The Criterion Approach to Unraveling Beta and Alpha Change - Vliert, Evert Van de; Huismans, Sipke E.; Stok, Jan J. L. (Academy of Management Review, 1985)
Three types of change that occur with self-reported pre-post-intervention data are reconceptualization (gamma change), scale recalibration (beta change), and actual increase or decrease (alpha II change). Beta change is shown to have occurred if a beta change criterion is theoretically and empirically related to the shifts in the focal variable. It is suggested that correlations between shifts on a criterion and a focal variable are a means for estimating the relative size of beta and alpha change.